2013
DOI: 10.1111/jace.12688
|View full text |Cite
|
Sign up to set email alerts
|

Coloration and Nonlinear Optical Properties of ZnTe Quantum Dots in ZnOTeO2P2O5 Glasses

Abstract: ZnO–TeO2–P2O5 glasses were prepared by melt‐quenching method. The color of the glass samples changed from colorless to pale red and dark red with increasing TeO2 content. Coloration mechanism and nonlinear optical properties of ZnO–TeO2–P2O5 glasses have been investigated. Raman spectra and transmission electron microscope measurements indicated the precipitation of ZnTe quantum dots in the glasses and ZnTe quantum dots are the origin of coloration. Z‐scan technique was used to examine the nonlinear optical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…TeO 2 glasses are promising low phonon hosts for rare‐earth elements 1,16‐23 or present luminescence properties themselves 2 . Having a broadband NIR emission and a lifetime of tens of microseconds, Te glasses of different compositions (zinc oxide, phosphate, vanadate, borate, etc) may be promising material for fabricating broadband optical fibers, amplifiers, windows, lenses or tunable lasers in visible (Vis) 3‐10,24‐27 or in infrared (IR) domain 11,24,28 …”
Section: Introductionmentioning
confidence: 99%
“…TeO 2 glasses are promising low phonon hosts for rare‐earth elements 1,16‐23 or present luminescence properties themselves 2 . Having a broadband NIR emission and a lifetime of tens of microseconds, Te glasses of different compositions (zinc oxide, phosphate, vanadate, borate, etc) may be promising material for fabricating broadband optical fibers, amplifiers, windows, lenses or tunable lasers in visible (Vis) 3‐10,24‐27 or in infrared (IR) domain 11,24,28 …”
Section: Introductionmentioning
confidence: 99%
“…For the first time, Kim and Yoon reported the extraordinarily high level of 3rd-NLO responses of zeolite-intercalated PbS QDs [26]. Thus, the nonlinear refractive ( ) and absorption ( ) coefficients of the zeolite-intercalated PbS QDs, the two important properties of 3rd-NLO materials, are ∼20 to 330 times higher than the highest values obtained from other QD-dielectric matrix systems [12][13][14][15][16][17][18][19][20][21][22][23] at 532 and 1064 nm, respectively. Moreover, very recently, Lee and Kim [27] demonstrated that the electric field strength, framework donor strength, and cation acceptor strength in zeolites as the QD host could be sensitively and systematically changed via varying cation species in the zeolite framework.…”
Section: Introductionmentioning
confidence: 93%
“…This could be attributed to not only their quantum size effects but also their interface and surface structure. Some representative QDs include PbS [12], PbSe [13], CdS [14], CdSe [15], CdTe [16], ZnS [17], ZnSe [18], ZnTe [19], In 2 S 3 [20], CuS [21], and so forth [22,23]. However, the 3rd-NLO response values that have been reported so far do not meet the simultaneous requirement of large and fast 3rd-NLO responses for being useful in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to robust linear optical properties, ZnTe QDs are also expected to have large third-order optical nonlinearity (χ (3) ). 25 Du et al 26 reported NLO properties of ZnTe QDs trapped in ZnO−TeO 2 −P 2 O 5 (ZTP) glasses, however, there was no control over particle sizes and the optical absorption spectra were too broad. We previously reported a unique supersaturation-controlled method to synthesize highly monodisperse, water-soluble ZnTe QDs with enhanced tunability of size and luminescence.…”
Section: Introductionmentioning
confidence: 99%